Danish premature birth rates during the COVID-19 lockdown. Issue 1 (11th August 2020) - Hedermann, Gitte; Hedley, Paula Louise; Bækvad-Hansen, Marie; Hjalgrim, Henrik; Rostgaard, Klaus; Poorisrisak, Porntiva; Breindahl, Morten; Melbye, Mads; Hougaard, David M; Christiansen, Michael; Lausten-Thomsen, Ulrik
Abstract : To explore the impact of COVID-19 lockdown on premature birth rates in Denmark, a nationwide register-based prevalence proportion study was conducted on all 31 180 live singleton infants born in Denmark between 12 March and 14 April during 2015–2020. The distribution of gestational ages (GAs) was significantly different (p=0.004) during the lockdown period compared with the previous 5 years and was driven by a significantly lower rate of extremely premature children during the lockdown compared with the corresponding mean rate for the same dates in the previous years (OR 0.09, 95% CI 0.01 to 0.40, p<0.001). No significant difference between the lockdown and previous years was found for other GA categories. The reasons for this decrease are unclear. However, the lockdown has provided a unique opportunity to examine possible factors related to prematurity. Identification of possible causal mechanisms might stimulate changes in clinical practice.